EFFECTIVE WAYS OF REHABILITATION WORK WITH CHILDREN WITH COCHLEAR IMPLANTS - M. R. Po‘latkhodjaeva (Journals Park Publishing, 2022)
The sooner a hearing-impaired child is involved in the rehabilitation process, the faster his social adaptation will be. If parents are given practical help to overcome psychological obstacles, if they realize in time that their children need corrective and developmental help in addition to medical help, then the child's skills of understanding speech and communicating through speech will be formed early.